REUSING PHOSPHATE MINE TAILINGS IN MEMBRANE FILTER PRODUCTION: MICROSTRUCTURE AND FILTRATION APPROPRIATENESS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Because of their strong mechanical, chemical, and thermal resilience, ceramic membrane filters made of industrial by-products can be viewed as a valuable substitute for phosphate mine tailings. This is especially true if the ceramic membranes are employed in the treatment of industrial wastewater. This method's ability to depollute textile industry rejects hasn't been thoroughly investigated before. In this project, phosphate mine tailings (phosphate sludge) and natural clay were used to create ceramic membrane filters. The aforementioned materials were blended with sawdust, up to 20 weight percent, as a pore-forming agent, and the results were examined in the 900–1100 ◦C range by means of thermal analysis, X-ray diffraction, scanning electron microscopy, and mercury porosimetry. The relationship between firing temperature and sawdust addition was seen in the ceramic characteristics. Tests of filtration were performed on samples that had favorable characteristics. The findings demonstrated that calcium phosphate originated from partial fluorapatite decomposition, whereas gehlenite and diopside were generated from carbonates that were broken down by lime and clay mineral breakdown products. Fluorapatite and quartz both resisted heat. The experimental design results demonstrated that the polynomial model provided a good description of the differences in physical attributes versus processing parameters. The fascinating filtration results make these membranes suitable for application in the treatment of industrial wastewater. Phosphate mine tailings are often considered waste materials with limited reuse potential. However, this study explores their application in the production of membrane filters, which are essential for various filtration processes. This paper discusses the materials and techniques used to evaluate the microstructure of phosphate mine tailings and their appropriateness for filtration applications.